Electrochemistry of cytochrome P450 17α-hydroxylase/17, 20-lyase (P450c17). (5th February 2017) - Martin, Lisandra L.; Kubeil, Clemens; Simonov, Alexandr N.; Kuznetsov, Vladimir L.; Corbin, C. Jo; Auchus, Richard J.; Conley, Alan J.; Bond, Alan M.; Rodgers, Raymond J.
Abstract: Within the superfamily of cytochrome P450 enzymes (P450s), there is a small class which is functionally employed for steroid biosynthesis. The enzymes in this class appear to have a small active site to accommodate the steroid substrates specifically and snuggly, prior to the redox transformation or hydroxylation to form a product. Cytochrome P450c17 is one of these and is also a multi-functional P450, with two activities, the first 17α-hydroxylation of pregnenolone is followed by a subsequent 17, 20-lyase transformation to dehydroepiandrosterone (DHEA) as the dominant pathways to cortisol precursors or androgens in humans, respectively. How P450c17 regulates these two redox reactions is of special interest. There is a paucity of direct electrochemical studies on steroidogenic P450s, and in this mini-review we provide an overview of these studies with P450c17. Historical consideration as to the difficulties in obtaining reliable electrochemistry due to issues of handling proteins on an electrode, together with advances in the electrochemical techniques are addressed. Recent work using Fourier transformed alternating current voltammetry is highlighted as this technique can provide both catalytic information simultaneously with the underlying redox transfer with the P450 haem. Highlights: Direct electrochemistry links structure, activity and multi-functionality of P450c17. New methods overcome the challenges for physiologically relevant redox data. FT ac Voltammetry (FTacV) allows new insights to P450 enzyme catalysis.